Kualitas Sumberdaya Aparatur Sipil Negara Dalam Pelayanan Administrasi Di Kantor Kelurahan Pandu - Kapoh, Willy; Liando, Daud; Waleleng, Grace (JURNAL ILMIAH SOCIETY, 2016)
This study aims to determine the quality of civilian personnel resources of the State in the administrative services at the Village Office Pandu District of Bunaken, Manado. The method used is a qualitative research method. Research techniques using triangulation method. The results showed that the quality of Administrative Resources in the State civil administrative services at the Village Office Pandu still not been implemented properly. This is due to the work possessed knowledge has not kept pace with the skills and ability to perform their duties, due in part to the State Civil Apparatus has not mastered the technical and operational jobs, high discipline, loyalty to the job and work responsibilities. Keywords: Quality, Service